Compulsory notification of paracoccidioidomycosis: A 14‐year retrospective study of the disease in the state of Paraná, Brazil - Suguiura, Igor Massahiro Souza; Ono, Mario Augusto (Mycoses, 2022)
Background Paracoccidioidomycosis, caused by fungi of the Paracoccidioides genus, is one of the most important endemic mycoses in Brazil. The disease is not of mandatory reporting in the country; however, some Brazilian states, such as Paraná, have included it on their local lists of public health‐reportable diseases. Objective Describe the epidemiology of the positive paracoccidioidomycosis cases in the state of Paraná based on analysis of reporting forms and mortality data. Subjects and methods Data of positive cases of state residents 2007–2020 were obtained from public health databases and frequency, incidence, geographic distribution, mortality and trends were analysed. Mortality of the disease was also compared to other mycoses such as cryptococcosis, aspergillosis, histoplasmosis, candidiasis and sporotrichosis. Results 670 patients were positive for the disease. The cumulative and average annual incidence was, respectively, 6.4 and 0.46 cases/100,000 inhabitants. The new cases of paracoccidioidomycosis were reported mainly by specialised health units, including tertiary centres, and 285 days was the mean from the beginning of the symptoms until the diagnosis. The western region showed the highest incidence and mortality by the disease over the other state mesoregions. During the period, a decreasing trend was observed in the confirmed cases and stability in the mortality rate with an average annual mortality of 1.17 per million/inhabitants in the state; however, paracoccidioidomycosis had the highest mortality when compared to other mycoses. Conclusions Paracoccidioidomycosis is an important endemic mycosis in Paraná and this study provides an epidemiological baseline for future modifications of paracoccidioidomycosis surveillance.